Collaborative care in schools: enhancing integration and impact in youth mental health. Issue 3 (1st October 2016) - Lyon, Aaron R.; Whitaker, Kelly; French, William P.; Richardson, Laura P.; Wasse, Jessica Knaster; McCauley, Elizabeth
Abstract: Collaborative care (CC) is an innovative approach to integrated mental health service delivery that focuses on reducing access barriers, improving service quality and lowering health care expenditures. A large body of evidence supports the effectiveness of CC models with adults and, increasingly, for youth. Although existing studies examining these models for youth have focused exclusively on primary care, the education sector is also an appropriate analogue for the accessibility that primary care offers to adults. CC aligns closely with the practical realities of the education sector and may represent a strategy to achieve some of the objectives of increasingly popular multi-tiered systems of supports frameworks. Unfortunately, no resources exist to guide the application of CC models in schools. Based on the existing evidence for CC models, the current paper (1) provides a rationale for the adaptation of CC models to improve mental health service accessibility and effectiveness in the education sector; (2) presents a preliminary CC model for use in schools; and (3) describes avenues for research surrounding school-based CC, including the currently funded Accessible, Collaborative Care for Effective School - based Services project.